Efficacy of the educational program “for a happy uterus” to improve knowledge and attitudes towards the vaccine of human papilloma virus in students of the fifth grade of primary school of the Institución Educativa Las Mercedes, Juliaca - Huanca Yanapa, Yessica (2019)
Objetives: determine the effectiveness of the educational program “for a happy uterus” to improveknowledge, attitudes towards Vaccine Human Papilloma students in the fifth grade of School“Mercedes” compared to a control group. Materials and Methods: the methodology was qualitativewith quasi-experimental research design; in a sample of 60 school women, to collect the data thesurvey technique in which a pre-test and post-test, both the control and experimental group wereapplied was used. Results: in the pretest are: 90.6% had a low level, followed by a 9.4% showed amedium level and 0% to a high standard and attitude showed: 59.4% rejection, followed by a 34.4%presented indifference and 6.3% presented acceptance; after the intervention in the post-test stage,the following results were obtained: A 96.9% had a high level, followed by a 3.1% having an averagelevel and 0% of schoolchildren presented a low and attitude level 93.8% showed acceptance, followedby a 6.3% showed indifference and rejection shows 0%. Applying the T test for related samples thealternative hypothesis is accepted. Conclusions: that the educational program “for a happy uterus” iseffective in improving knowledge and attitudes towards HPV vaccine in school.